2022
DOI: 10.1186/s12985-022-01875-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal epidemiological and clinical characteristics of pediatric patients with human parainfluenza virus infection by serotype: a retrospective study

Abstract: Background The development of the polymerase chain reaction (PCR) test promoted the evaluation of the epidemiological and clinical characteristics of human parainfluenza virus (HPIV) type 4, which has been rarely studied using conventional diagnostic methods. This study aimed to determine the seasonal epidemiological and clinical characteristics of all four HPIV serotypes (HPIV-1, HPIV-2, HPIV-3, and HPIV-4) during the era of PCR testing. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
4
2
0
Order By: Relevance
“…Despite its lower prevalence, overall, in the pre-pandemic period, HPIV 3 was the most prevalent, causing infection in very young children throughout the study period, accounting for 47% of infections in the 0-6-month age group (2014-2019) and 73% in this age group between 2020 and 2022. This is concordant with findings in other studies, including one from South Africa, which also sug-gest that HPIV 3 infections occur early in life [17,20]. HPIV 3 and 4 viruses each displayed distinct seasonality, with HPIV 3 activity mainly in late winter/spring and HPIV 4 mainly in autumn in the pre-COVID period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite its lower prevalence, overall, in the pre-pandemic period, HPIV 3 was the most prevalent, causing infection in very young children throughout the study period, accounting for 47% of infections in the 0-6-month age group (2014-2019) and 73% in this age group between 2020 and 2022. This is concordant with findings in other studies, including one from South Africa, which also sug-gest that HPIV 3 infections occur early in life [17,20]. HPIV 3 and 4 viruses each displayed distinct seasonality, with HPIV 3 activity mainly in late winter/spring and HPIV 4 mainly in autumn in the pre-COVID period.…”
Section: Discussionsupporting
confidence: 92%
“…This prevalence of infection is comparable with findings in other parts of the world where reported prevalence of HPIV in hospitalized children with ARI is estimated to vary between 4 and 14% [5]. The median age of infection of 0.86 years in positive children between 2016 and 2022 is similar to that reported in other low and middle income countries [5,14], but infections in age groups younger than that is seen in more developed nations, where the majority of infections are reported to occur in the 1-5-year age group [14][15][16][17][18]. This could reflect higher transmissibility of infection due to crowded living conditions and greater difficulty in applying measures to limit the spread of infections in lower socio-economic environments.…”
Section: Discussionsupporting
confidence: 58%
“…In this study, prevalence of coronaviruses in 2020–2021 showed that they are common in winter similar to the results we found in our study. The HPiV is commonly found in November which is similar to other reports in the literature 20,22 . Our study HMPV cases were identified in winter which is not seen by seasonal spreading; however, in some cases, it was reported to happen more in summer 23,24 …”
Section: Discussionsupporting
confidence: 90%
“…The HPiV is commonly found in November which is similar to other reports in the literature. 20,22 Our study HMPV cases were identified in winter which is not seen by seasonal spreading; however, in some cases, it was reported to happen more in summer. 23,24 Similar to Ntagereka et al, we did not find differences in the clinical behavior and viruses' infection except for sore throat (0.028), headache (p = 0.016), and body pain (p = 0.0001), either.…”
Section: Moreover Hpiv Andmentioning
confidence: 59%
“…A systemic review in 2021 estimated that infection with HPIV1–4 caused approximately 13% of acute lower respiratory infection (ALRI) cases, 4 to 14% of ALRI hospital admissions, and 4% of ALRI mortality worldwide among children younger than 5 years ( 5 ). Generally, HPIV2 prevalence was ranked after HPIV3 and HPIV1, accounting for 2.6 to 14% of HPIV infections, depending on the case definition, detection method, and duration of the studies ( 6 to 9 ). However, due to the lack of systematic surveillance, the disease burden of HPIV2 in China remains unclear.…”
Section: Introductionmentioning
confidence: 99%